Merengkuh Yang Lain: Dialog Interreligius Dan Transformasi Diri Terhadap Yang Lain - Danang Kristiawan (Sekolah Tinggi Teologi Sriwijaya, 2020)
An issue that has been a discussion in interreligious dialogue is about how we creatively frame the tensions between the identity and the solidarity, the commitment and the openness, the uniqueness and the togetherness, the particularity and the universality each religion. That tensions create a trade-off between the universalism and the particularism. The universalism assumes that there is a common ground as the prerequisite of the dialogue found inside or outside the religions. On the other side, particularism understands that every religion is unique and different. It forms the experience of the community and can only be understood by the community itself. Both opposite viewpoints are important to acknowledge in order to keep the creative tensions between the identity and the solidarity in the interreligious dialogue. The following writing will explain some efforts to bridge the tensions between the identity and the solidarity in the interreligious dialogue. Furthermore, the writing will present the imagination of “embrace” by Miroslav Volf as an appreciative-critical-transformative interreligious dialogue. It includes some notes of how interreligious embrace can be done in practice.